HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KEPEMIMPINAN: SEBUAH TINJAUAN SISTEMATIS - Sintya, Rani; Wardi, Yunia; Thaib, Ilham (Jurnal Ekonomi Manajemen, 2023)
Emotional intelligence (EQ) has become an interesting topic in leadership research because of its ability to influence the performance and effectiveness of a leader. This systematic review aims to investigate the relationship between emotional intelligence and leadership by analyzing the relevant literature. In this review, researchers conducted a literature search through different databases and selected studies that met the inclusion criteria. After going through the selection process, an analysis was conducted of the relevant articles to identify the main findings. The findings from this review indicate a positive relationship between emotional intelligence and leadership. Emotional intelligence plays an important role in developing and enhancing effective leadership. Emotional intelligence can help leaders make better decisions, communicate more effectively, build good relationships with team members, and handle conflicts better. This has a positive impact on the performance of individuals and groups led by leaders who have high emotional intelligence.